Pengaruh Celebrity Endorser, Video Advertising Terhadap Keputusan Pembelian Sepatu Vans (Studi Kasus Pada Mahasiswafeb Angakatan 2019 Unisma) - Muhammad Ilham Habibi; Budi Wahono; M. Khoirul Anwarudin Broto Suharto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study was conducted to examine the influence  of celebrity endorsers, video advertising  on vans shoe purchase decisions (case study on students of the Faculty of Economics and Business Class of 2019 Islamic University of Malang). The population in this study was 904 college students. The sampling technique used was Purposive Sampling and 98 students were obtained. The data collection method used is the distribution of questionnaires. The results showed that the results of the simultaneous test or F test simultaneously  variable Celebrity Endorse, and Vidio Advertising, simultaneously affect the purchasing decision of Islamic University of Malang students.The results obtained in this study can be concluded that partially celebrity endorse (X1) has a significant positive effect on purchasing decisions. The results obtained in this study can be concluded that partially Vidio Advertising (X2) has a significant positive effect on purchasing decisions. Keywords: Celebrity Endorser, Video Advertising, Purchase Decision